The Influence of the Number of Tourist Visits on Regional Original Income (PAD) in the Tourism Sector in Deli Serdang District, 2020–2024 - Harahap, Nursakila; Silaban, Devy Kristina; Situmorang, Harlan N (International Journal of Sustainable Competitiveness on Tourism, 2026)
This study aims to analyze the influence of the number of tourist visits on the Regional Original Income (PAD) in the tourism sector in Deli Serdang Regency for the 2020–2024 period. The study was conducted using a quantitative approach with simple linear regression analysis based on official data on the number of tourists and tourism PAD over five years. The results show that the number of tourist visits has a positive and significant influence on the PAD in the tourism sector. The increase in tourist visits is consistently followed by an increase in the PAD contribution, although there are fluctuations during the post-pandemic recovery period. The coefficient of determination indicates that most of the variation in PAD can be explained by the number of tourists arriving, while other factors have only a small influence. These findings reinforce the importance of the tourism sector as a crucial component in supporting regional income, thus requiring the government to strengthen destination development strategies and sustainable tourism governance to maximize regional economic potential.